1998
DOI: 10.1007/978-3-662-03543-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Conservation Biology of Coastal Transition Zones from Mediterranean to Desert Ecosystems: An Intercontinental Comparison

Abstract: Comparative research on Mediterranean-type ecosystems over the past several decades has largely focused on evergreen, sclerophyllous vegetation. Little attention has been given to comparative research on ecological structure and community diversity in the coast al transitions from mediterranean climate zones to winter rainfall deserts. This has been a particularly important oversight by the MEDECOS research community, since the Mediterranean desert transition zones are potentially as diverse as their related "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Northwest Baja California, Mexico, where Mediterranean coastal vegetation continues southward from California, has also experienced recent accelerated development. As a result few undisturbed coastal lands exist on either side of the border (Reid & Murphy 1995; Esler et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Northwest Baja California, Mexico, where Mediterranean coastal vegetation continues southward from California, has also experienced recent accelerated development. As a result few undisturbed coastal lands exist on either side of the border (Reid & Murphy 1995; Esler et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…1) (SEDUE 1989; Halvorson 1994). Consequently, these islands hold potential for the conservation of California Mediterranean coastal ecosystems (Esler et al 1998; Walter 1998). Restoration has been underway on U.S. California Islands for over 15 years (Davis et al 1994; Halvorson 1998), and recent efforts have demonstrated the conservation value of islands in northwest Mexico (Donlan et al 2000; Tershy et al 2002; Donlan et al in press).…”
Section: Introductionmentioning
confidence: 99%
“…This community becomes lower and m ore scrubby on drier slopes, and mostly arboreal in shaded canyon ("quebradas") where moisture levels are higher (Esler et al, 1998). The site is located in a degraded area dom inated by low sclerophyll forest ("m atorral").…”
Section: Introductionmentioning
confidence: 99%